Rate of Convergence of Hermite-Fejér Interpolation on the Unit Circle - E. Berriochoa; A. Cachafeiro; J. Díaz; E. Martínez-Brey (Journal of Applied Mathematics)
The paper deals with the order of convergence of the Laurent polynomials of Hermite-Fejér interpolation on the unit circle with nodal system, the n roots of a complex number with modulus one. The supremum norm of the error of interpolation is obtained for analytic functions as well as the corresponding asymptotic constants.